Proposal for a development plan for the Peruvian forestry sector - Ramirez-Arroyo, Rafael (2021)
The objective of this study was to develop a proposal for the National Forest and Wildlife Plan as a contribution to the mandate established in Law No. 29763. For this purpose, a qualitative descriptive method was used where a socio-economic, environmental diagnosis has been made and budgetary-institutional sector, to then be compared with global trends set by FAO. The main results indicate that, although an important group of entrepreneurs are increasing the production of products other than wood, those dedicated to wood production persist in producing goods that have had a clear decreasing trend worldwide. Another important aspect is the importance that environmental services have been acquiring with greater relevance, particularly those related to conservation and ecotourism, evidenced in the increase in natural protected areas, to the point that they currently occupy these 22 252 077 ha. In relation to forestry institutions, this is very leafy and even though the public budget has increased in the last 11 years by 4.76 times, a better institutional, process and budget articulation is still necessary. In conclusion, to overcome these limitations, it is necessary that the forest development plan involves an adequate territorial ordering, an information system oriented to promotion, but also to the control of trade, a greater formal and real occupation of the territory, as well as the promotion of certified management areas, productive forest plantations and provision of environmental services, among other measures.